PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR DAN KREATIVITAS PADA MATERI PENGELOLAAN LIMBAH - Anis Fadhil Faisal Rahmatillah; Aminuddin Prahatama Putra; Amalia Rezeki (Jurnal Genta Mulia, 2026)
This study aims to improve learning outcomes and creativity of students by implementing two cycles. Product cognitive learning outcomes in cycle one showed that the N-gain of students was 0.03 with a low category, in the second cycle there was an increase in students' cognitive learning outcomes of 0.78 with a high category. Process cognitive learning outcomes showed an increase from an average value of 49 in cycle one to 73 in the second cycle, there was a significant increase when learning took place. Affective learning outcomes in cycle one amounted to 93.55% for the less category and 6.45% for the sufficient category, in the second cycle there was an increase of 25.81% for the very good category and 74.19% for the good category. Affective learning outcomes in each indicator showed an increase in the average percentage in cycle one of 31.31% to 72.34%. Psychomotor learning outcomes in cycle one with a percentage of 80.56% for the less category, 16.13% for the sufficient category and 3.23% for the good category, in the second cycle there was an increase with a percentage of 61.29% for the excellent category and 38.71% for the good category. Psychomotor learning outcomes showed an increase from cycle one in each indicator by 27.92% to 86.67% from cycle two. The results of students' creativity with a percentage of 83.87% for the less category and 16.13% for the sufficient category, in the second cycle the increase in students' creativity was 67.74% for the very good category and 32.26% for the good category. The results of students' creativity in each aspect with an average percentage of 26.90% in cycle one to 66.56% in cycle two, this shows that the PjBL model can increase students' creativity so that the PjBL model can be used as an effective alternative in improving the quality of learning in schools.